Relationship between Intestinal Helminthiasis and Hemoglobin Level among Primary School Children in Sokoto Metropolis - O. F. Ashcroft; M. Bello; A. E. Ahmad; N. M. Bunza; A. A. Ahmed (Archives of Current Research International, 2018)
Intestinal helminthes are associated with the reduction in the level of haemoglobin. This abnormal reduction in haemoglobin results in anemia. The study determined the prevalence of parasitic infection and its relationship with haemoglobin level among primary school children in Sokoto metropolis. Stool and blood samples were collected from 224 children from some selected primary schools in Sokoto Metropolis. The stool specimens were examined for parasites by both macroscopic and microscopic methods (saline and wet iodine mount, and formol-ether concentration) while haemoglobin concentration in the blood sample was estimated using hemocue hemoglobin method. A prevalence rate of 8.5% was seen among the children sampled. Hookworm had the highest prevalence of 3.1%, followed by Hymenolepis nana (1.8%). Ascaris lumbricoides had a prevalence of 1.3%, Schistosoma mansoni (0.9%) and Strongyloides stercoralis (0.4%). 0.9% showed mixed infection with H. nana and Hookworm. Children within the age group of 4-6years had the highest prevalence rate (60%). Male children had a higher prevalence (4.5%) than female (4.0%). The mean haemoglobin concentration in the healthy subject was 11.82 g/dl, while in infected subjects it was 11.03 g/dl, the difference was statistically significant (p<0.05). The study demonstrated that there was a low prevalence of intestinal helminthiasis among children in Sokoto metropolis. However, the haemoglobin concentrations of infected children were significantly affected by parasitic infection. Low haemoglobin concentration in children can lead to behavioural disturbances as a result of impaired neurological development and reduced scholastic performance. Based on these findings, efforts must be made to create better sanitary and toilet facilities in schools at all times to avoid indiscriminate defecation that could lead to the transmission of helminthic infections.